Effective car monitoring and tracking model - Hameed, Shihab A.; Abdalla, Shaima; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Daoud, Jamal Ibrahim (INSI Publications, 2012)
Statistics shows that car production in the world is the increasing yearly as well as car theft attempts. Many international and local companies have good effort in term of producing car security systems, but the result is still less than expectations since the number of car theft cases are still increases. The thieves are developing their capabilities and inventing smarter and stronger stealing techniques which require more powerful security systems. On the other hand most of the cars use traditional alert systems (with no mobility or multimedia facilities) as well as the advanced car security system are still expensive and mainly used in expensive cars. To overcome such problems; this research project proposes a New Car Monitoring and Tracking Model. It introduces a powerful security model that can send SMS and MMS to the owner or security organizations to have fast response especially if the car is nearby. This paper focuses on using SMS, MMS and database technology, the picture of the intruder will be sent to user or police. The Database offers the required information about car and owner, which will help police or security authorities in tracking the car using GPS system that can be link to Google Earth and other mapping software. The implementation and testing results show the success of prototype in sending SMS and MMS to owner within seconds and receiving acknowledgment to the database (police or security unit) within 3-4 minutes. The timing and results are suitable to owner and police to take suitable action against intruder.